Economic, social and environmental ex ante impacts of scaling mechanized direct-seeded rice technology package : evidence from Cambodia - Oyakhilomen Oyinbo; Chamberlin, Jordan; Gbegbelegbe, Sika; Flor, Rica J. (EiA, 2024)
Direct broadcast seeding, the dominant rice establishment method among smallholder farmers in Southeast Asia, is associated with suboptimal rice productivity, profitability and environmental sustainability. Mechanized direct-seeded rice with complementary agronomic management practices, has been proposed to address these challenges and improve outcomes relative to those of broadcast seeded rice. Yet there is sparse evidence to date on the potential impacts of scaling this technology package, particularly from a sustainability lens. This study assesses the potential economic, social and environmental impacts of scaling the mechanized direct-seeded rice technology package in Cambodia. We use data from on-farm validation trials, a baseline farm-household survey, and secondary sources to parameterize a partial equilibrium economic surplus model to estimate the potential impacts. Results show that investments in scaling the technology package can generate high economic returns, reduce the number of poor people, and substantially mitigate carbon dioxide equivalent emissions. These findings hold even under lower- and higher-than expected yield and input cost changes, which allow for variability in expected investment returns. In addition, the results show considerable variation in potential economic returns between the provinces in Cambodia, which indicates that spatial context likely matters in the potential investment returns. Overall, our findings suggest that policy interventions to promote wider adoption of the technology package are vital entry points to harnessing the potential benefits of the mechanized direct-seeded rice technology package.